Development and certification of a pharmacopoeial reference standard for primary structure identification of purified recombinant interferon beta-1b by peptide mapping - E. O. Goloshchapova; O. B. Rounova; A. S. Minero; O. V. Fadeikina; R. A. Volkova; M. B. Degterev; S. A. Taran; R. R. Shukurov; O. B. Ustinnikova (Биопрепараты: Профилактика, диагностика, лечение, 2022)
Medicines based on recombinant human interferons (rhIFNs) beta-1a and beta-1b are used as first-line treatment of multiple sclerosis. Meanwhile, rhIFN beta-1a and beta-1b have structural differences associated with the eukaryotic or prokaryotic expression systems, respectively. Pharmacopoeias require identification of the primary structure of recombinant proteins by peptide mapping, which involves the use of reference material. Currently, there is no international reference standard available for rhIFN beta-1b structural identification. The aim of the study was development and certification of a pharmacopoeial reference standard for identification of the amino acid sequence of purified rhIFN beta-1b by peptide mapping. Materials and methods: rhIFN beta-1b produced by GENERIUM and endoproteinase Glu-C from Staphylococcus aureus V8 were used in the study. The peptide mapping was performed using reverse-phase high-performance liquid chromatography (RP HPLC) and high-resolution mass spectrometry. Statistical evaluation of the results included calculation of the arithmetic mean, standard deviation, and coefficient of variation. Results: the authors developed and certified a Russian Pharmacopoeia reference standard for structural identification of rhIFN beta-1b (PhRS 3.2.00447). The certified characteristic is the range of retention times of characteristic peaks: the absolute retention time was 42.0–43.2 for the third (reference) peak, the relative retention time was 0.61–0.66 for the first peak, 0.68–0.73 for the second peak, 1.04–1.06 for the fourth peak, 1.14–1.15 for the fifth peak, 1.22–1.24 for the sixth peak, and 1.29–1.30 for the seventh peak. Conclusions: the authors developed requirements for the rhIFN beta-1b pharmacopoeial reference standard. The material chosen as the candidate reference standard was an intermediate rhIFN beta-1b product sampled before addition of human serum albumin. The quality control was carried out in accordance with the developed specification. The authors analysed the amino acid sequence of the molecule, confirmed the presence of the disulfi e bond, and obtained the certifi d characteristic of the reference standard. Comparative analysis of the peptide maps of the certified rhIFN beta-1b pharmacopoeial reference standard and the rhIFN beta-1a reference standard revealed differences between the maps, and, therefore, confirmed the relevance of the developed reference standard.